How drought severity constrains GPP and its partitioning among carbon pools in a Quercus ilex coppice? - Rambal, S; Lempereur, M; Limousin, J M; Martin-StPaul, N K; Ourcival, J M; Rodríguez-Calcerrada, J (Biogeosciences Discuss., 2014)
The partitioning of photosynthates toward biomass compartments has a crucial role in the carbon sink function of forests. Few studies have examined how carbon is allocated toward plant compartments in drought prone forests. We analyzed the fate of GPP in relation to yearly water deficit in an old evergreen Mediterranean Quercus ilex coppice severely affected by water limitations. Gross and net carbon fluxes between the ecosystem and the atmosphere were measured with an eddy-covariance flux tower running continuously since 2001. Discrete measurements of litterfall, stem growth and fAPAR allowed us to derive annual productions of leaves, wood, flowers and acorns and an isometric relationship between stem and belowground biomass has been used to estimate perennial belowground growth. By combining eddy-covariance fluxes with annual productions we managed to close a C budget and derive values of autotrophic and heterotrophic respirations, NPP and carbon use efficiency (CUE, the ratio between NPP and GPP). Average values of yearly NEP, GPP and Reco were 282, 1259 and 977 g C m−2. The corresponding ANPP components were 142.5, 26.4 and 69.6 g C m−2 for leaves, reproductive effort (flowers and fruits) and stems. Gross and net carbon exchange between the ecosystem and the atmosphere were affected by annual water deficit. Partitioning to the different plant compartments was also impacted by drought, with a hierarchy of responses going from the most affected, the stem growth, to the least affected, the leaf production. The average CUE was 0.40, which is well in the range for Mediterranean-type forest ecosystems. CUE tended to decrease more slightly in response to drought than GPP and NPP, probably due to drought-acclimation of autotrophic respiration. Overall, our results provide a baseline for modeling the inter-annual variations of carbon fluxes and allocation in this widespread Mediterranean ecosystem and highlight the value of maintaining continuous experimental measurements over the long term.
APS
Keywords: carbon sink; Drought; GPP; photosynthates; Quercus ilex

Evaluation of the potential of MODIS satellite data to predict vegetation phenology in different biomes: An investigation using ground-based NDVI measurements - Hmimina, G; Dufrêne, E; Pontailler, J.-Y.; Delpierre, N; Aubinet, M; Caquet, B; de Grandcourt, A; Burban, B; Flechard, C; GRANIER, a; Gross, P; Heinesch, B; et al. (Remote Sensing of Environment, 2013)
Abstract Vegetation phenology is the study of the timing of seasonal events that are considered to be the result of adaptive responses to climate variations on short and long time scales. In the field of remote sensing of vegetation phenology, phenological metrics are derived from time series of optical data. For that purpose, considerable effort has been specifically focused on developing noise reduction and cloud-contaminated data removal techniques to improve the quality of remotely-sensed time series. Comparative studies between time series composed of satellite data acquired under clear and cloudy conditions and from radiometric data obtained with high accuracy from ground-based measurements constitute a direct and effective way to assess the operational use and limitations of remote sensing for predicting the main plant phenological events. In the present paper, we sought to explicitly evaluate the potential use of MODerate resolution Imaging Spectroradiometer (MODIS) remote sensing data for monitoring the seasonal dynamics of different types of vegetation cover that are representative of the major terrestrial biomes, including temperate deciduous forests, evergreen forests, African savannah, and crops. After cloud screening and filtering, we compared the temporal patterns and phenological metrics derived from in situ NDVI time series and from MODIS daily and 16-composite products. We also evaluated the effects of residual noise and the influence of data gaps in MODIS NDVI time series on the identification of the most relevant metrics for vegetation phenology monitoring. The results show that the inflexion points of a model fitted to a MODIS NDVI time series allow accurate estimates of the onset of greenness in the spring and the onset of yellowing in the autumn in deciduous forests (RMSE ≤ one week). Phenological metrics identical to those provided with the MODIS Global Vegetation Phenology product (MDC12Q2) are less robust to data gaps, and they can be subject to large biases of approximately two weeks or more during the autumn phenological transitions. In the evergreen forests, in situ NDVI time series describe the phenology with high fidelity despite small temporal changes in the canopy foliage. However, MODIS is unable to provide consistent phenological patterns. In crops and savannah, MODIS NDVI time series reproduce the general temporal patterns of phenology, but significant discrepancies appear between MODIS and ground-based NDVI time series during very localized periods of time depending on the weather conditions and spatial heterogeneity within the MODIS pixel. In the rainforest, the temporal pattern exhibited by a MODIS 16-day composite NDVI time series is more likely due to a pattern of noise in the NDVI data structure according to both rainy and dry seasons rather than to phenological changes. More investigations are needed, but in all cases, this result leads us to conclude that MODIS time series in tropical rainforests should be interpreted with great caution.
Keywords: Crops; Deciduous forests; evergreen forests; Ground-based NDVI; MODIS; Phenology

Ground-based Network of NDVI measurements for tracking temporal dynamics of canopy structure and vegetation phenology in different biomes - Soudani, K; Hmimina, G; Delpierre, N; Pontailler, J.-Y.; Aubinet, M; Bonal, D; Caquet, B; de Grandcourt, A; Burban, B; Flechard, C; Guyon, D; GRANIER, a; et al. (Remote Sensing of Environment, 2012)
Plant phenology characterises the seasonal cyclicity of biological events such as budburst, ﬂowering, fructiﬁ- cation, leaf senescence and leaf fall. These biological events are genetically pre-determined but also strongly modulated by climatic conditions, particularly temperature, daylength and water availability. Therefore, the timing of these events is considered as a good indicator of climate change impacts and as a key parameter for understanding and modelling vegetation–climate interactions. In situ observations, empirical or bioclimatic models and remotely sensed time-series data constitute the three possible ways for monitoring the timing of plant phenological events. Remote sensing has the advantage of being the only way of surface sampling at high temporal frequency and, in the case of satellite-based remote sensing, over large regions. Nevertheless, exogenous factors, particularly atmospheric conditions, lead to some uncertainties on the seasonal course of surface reﬂectance and cause bias in the identiﬁcation of vegetation phenological events. Since 2005, a network of forest and herbaceous sites has been equipped with laboratory made NDVI sensors to monitor the temporal dynamics of canopy structure and phenology at an intra-daily time step. In this study, we present recent results obtained in several contrasting biomes in France, French Guiana, Belgium and Congo. These sites represent a gradient of vegetation ecosystems: the main evergreen and deciduous forest ecosystems in temperate climate region, an evergreen tropical rain forest in French Guiana, an herbaceous savanna ecosystem in Congo, and a succession of three annual crops in Belgium. In this paper, (1) we provide an accurate description of the seasonal dynamics of vegetation cover in these different ecosystems (2) we identify the most relevant remotely sensed markers from NDVI time-series for determining the dates of the main phenological events that characterize these ecosystems and (3) we discuss the relationships between temporal canopy dynamics and climate factors. In addition to its importance for phenological studies, this ground-based Network of NDVI measurement provides data needed for the calibration and direct validation of satellite observations and products.
Keywords: Crops; Evergreen and deciduous forests; Ground-based NDVI; Herbaceous savanna; NDVI time-series; Phenology; Tropical rain forest

Drought reduced monoterpene emissions from the evergreen Mediterranean oak Quercus ilex: results from a throughfall displacement experiment - a.-V. Lavoir; Staudt, M; Schnitzler, J P; Landais, D; Massol, F; Rocheteau, A; Rodriguez, R; Zimmer, I; Rambal, S (Biogeosciences, 2009)
The effects of water limitations on the emission of biogenic volatile organic compounds are not well understood. Experimental approaches studying drought effects in natural conditions are still missing. To address this question, a throughfall displacement experiment was set up in a natural forest of Quercus ilex, an evergreen Mediterranean oak emitting monoterpenes. Mature trees were exposed in 2005 and 2006 either to an additional drought, to irrigation or to natural drought (untreated control). In both years, absolute monoterpene emission rates as well as the respective standard factors of the trees exposed to normal and additional drought strongly declined during the drought periods. Monoterpene emissions were lower in year 2006 than in year 2005 (factor 2) due to a more pronounced summer drought period in this respective year. We observed a signiﬁcant difference between the irrigation and additional drought or control treatment: irrigated trees emitted 82% more monoterpenes during the drought period 2006 than the trees of the other treatments. However, no signiﬁcant effect on monoterpene emission was observed between normal and additional drought treatments, despite a signiﬁcant effect on leaf water potential and photochemical efﬁciency. During the development of drought, monoterpene emissions responded exponentially rather than linearly to decreasing leaf water potential. Emissions rapidly declined when the water potential dropped below −2 MPa and photosynthesis was persistently inhibited. Monoterpene synthase activities measured in vitro showed no clear reduction during the same period. From our results we conclude that drought signiﬁcantly reduces monoterpene ﬂuxes of Mediterranean Holm oak forest into the atmosphere due to a lack of primary substrates coming from photosynthetic processes
Keywords: BVOC emission; Drought; Quercus ilex (voyant); Water availability

Estimation of Photosynthetic Light Use Efficiency in Semi-Arid Ecosystems with the MODIS-Derived Photochemical Reflectance Index - Goerner, A; Reichstein, M; Rambal, S (Geoscience and Remote Sensing Symposium, 2008. IGARSS, 2008)
Direct estimations of light use efficiency from satellite data could reduce the uncertainties in data-oriented models of primary productivity. We analysed the potential of the photochemical reflectance index (PRI) based on MODIS data to approximate LUE of a Mediterranean Quercus ilex forest. Spectal band 1 (620-670 nm) turned out to be the best alternative reference band (the recommended 570 nm band does not exist on MODIS). Radiance correction with standard procedures (6S, dark object subtraction) did not improve the PRI-LUE relationship compared to the at-sensor reflectance version. The influence of surface anisotropy on the PRI signal was much reduced by constraining the observations to satellite data acquisitions with near nadir viewing angles.
Keywords: Drought; light use efficiency; photochemical reflectance index

Seasonal and annual variation of carbon exchange in an evergreen Mediterranean forest in southern France - ALLARD, V; Ourcival, J M; Rambal, S; Joffre, R; Rocheteau, A (Global Change Biology, 2008)
We present 9 years of eddy covariance measurements made over an evergreen Mediterranean forest in southern France. The goal of this study was to quantify the different components of the carbon (C) cycle, gross primary production (GPP) and ecosystem respiration (Reco), and to assess the effects of climatic variables on these fluxes and on the net ecosystem exchange of carbon dioxide. The Puéchabon forest acted as a net C sink of −254 g C m−2 yr−1, with a GPP of 1275 g C m−2 yr−1 and a Reco of 1021 g C m−2 yr−1. On average, 83% of the net annual C sink occurred between March and June. The effects of exceptional events such the insect-induced partial canopy defoliation that occurred in spring 2005, and the spring droughts of 2005 and 2006 are discussed. A high interannual variability of ecosystem C fluxes during summer and autumn was observed but the resulting effect on the annual net C budget was moderate. Increased severity and/or duration of summer drought under climate change do not appear to have the potential to negatively impact the average C budget of this ecosystem. On the contrary, factors affecting ecosystem functioning (drought and/or defoliation) during March–June period may reduce dramatically the annual C balance of evergreen Mediterranean forests.
Keywords: CO2 fluxes; eddy covariance; Mediterranean ecosystem; Quercus ilex

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H; Dufrêne, E; Francois, C; Le Maire, G; Loustau, D; Bosc, A; Rambal, S; GRANIER, a; Moors, E (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology

Summer and winter sensitivity of leaves and xylem to minimum freezing temperatures: a comparison of co-occurring Mediterranean oaks that differ in leaf lifespan. - Cavender-Bares, J; Cortés, P; Rambal, S; Joffre, R; Miles, B; Rocheteau, A (The New phytologist, 2005)
Freezing sensitivity of leaves and xylem was examined in four co-occurring Mediterranean oaks (Quercus spp.) grown in a common garden to determine whether freezing responses of leaves and xylem were coordinated and could be predicted by leaf lifespan. Freezing-induced embolism and loss of photosynthetic function were measured after overnight exposure to a range of subzero temperatures in both summer and winter. Both measures were found to be dependent on minimum freezing temperature and were correlated with leaf lifespan and vessel diameter. The dependence of xylem embolism on minimum freezing temperature may result from the decline in water potential with ice temperature that influences the redistribution of water during freezing and leads to an increase in xylem tension. Winter acclimatization had a relatively small effect on the vulnerability to freezing-induced embolism, although leaf photosynthetic function showed a strong acclimatization response, particularly in the two evergreen species. Quercus ilex, the species with the longest leaf lifespan and narrowest vessel diameters, showed the highest freezing tolerance. This helps explain its ability to inhabit a broad range throughout the Mediterranean region. By contrast, the inability of the deciduous oaks to maintain photosynthetic and vascular function throughout the winter indicates a competitive disadvantage that may prevent them from expanding their ranges.
Keywords: cold acclimatization; decline in F V /F M; freezing-induced embolism; leaf lifespan; minimum temperatures; xylem anatomy

The dehesa system of southern Spain and Portugal as a natural ecosystem mimic - Joffre, R; Rambal, S; Ratte, J P (Agroforestry Systems, 1999)
The dehesas of the southwestern Iberian Peninsula are ‘man-made’ ecosystems characterised by a savannah-like physiognomy. The trees are viewed as an integrated part of the system, and as a result are planted, managed, and regularly pruned. Palynological and historical evidence of the manipulation of initial ecosystems by man to obtain a savannah-like ecosystem is presented. The ecological functions of the tree are detailed using results obtained at two complementary scales. At the local scale, strong soil structural differences and functional differences in water budget and patterns of water use are observed under and outside the tree canopy. Using the concept of ecosystem mimicry, the two coexistent components of dehesas can be compared to two distant stages of a secondary succession characterised by very different behaviours. At the regional scale, evidence of relationships between tree density and mean annual precipitation over more than 5000 km2 suggests that the structure of these man-made agroecosystems have adjusted over the long-term and correspond to an optimal functional equilibrium based on the hydrological equilibrium hypothesis. Finally, the future of dehesas in the face of contemporary exogenous threats of economic and global environmental origin is discussed. 1. Introduction
Keywords: hydrological equilibrium; Mediterranean climate; optimality; Quercus ilex; Quercus suber; water balance

Exploring the relationships between reflectance and anatomical and biochemical properties in Quercus ilex leaves - Ourcival, J M; Joffre, R; Rambal, S (New Phytologist, 1999)
Leaf anatomical parameters such as leaf mass per area (LMA) and biochemical composition can be used as indicators of leaf photosynthetic capacity. The aims of this study are to evaluate the potential of reflectance spectroscopy of fresh leaves for assessing and predicting various parameters, anatomical (LMA and tissue thickness) and biochemical (nitrogen concentration). This paper describes results obtained with fresh leaves of holm oak (Quercus ilex), an evergreen oak that is widely distributed from mesic to xeric habitats in the Mediterranean. Fresh leaves (560) were collected over 3 yr at six different sites, from the top to the bottom of the canopy. The reflectance of each leaf was obtained within 1 h of sampling with an NIRSystems 6500 spectrophotometer over the range 400–2500 nm. LMA was determined for all samples; biochemical and anatomical measurements were conducted over representative subsample populations of 92 and 87 leaves, respectively. Stepwise regression calibrations and partial least squares (PLS) calibrations were developed and compared with different spectral regions and mathematical treatments. Calibration equations had high coefficients of determination (r2 ranging from 0.94 for nitrogen to 0.98 for LMA and tissue thickness). The PLS regressions gave better results than stepwise regressions for all parameters studied. Compared with regressions calculated on raw spectral data, calculations on second derivatives of spectra improved results in all cases. The use of scatter corrections also improved results. These results show that visible and near-infra red reflectance can be used for accurately predicting anatomical parameters and the nitrogen concentration of fresh holm oak leaves. The results support the suggestion that high spectral resolution imaging spectrometry can be a useful tool for assessing functional processes in forest ecosystems.
Keywords: Anatomy; infrared spectroscopy; Leaf mass per area; Quercus ilex; reflectance; Thickness

Seasonal and annual changes in leaf δ13C in two co-occurring Mediterranean oaks: relations to leaf growth and drought progression - Damesin, C; Rambal, S; Joffre, R (Functional Ecology, 1998)
1. Changes of δ13C and its relation to leaf development, biochemical content and water stress were monitored over a 2 year period in two co-occurring Mediterranean oak species: the deciduous Quercus pubescens and the evergreen Quercus ilex. 2. The time course of leaf δ13C showed different patterns in the two species. Young Q. pubescens leaves had a high δ13C and a marked decrease occurred during leaf growth. In contrast, leaves at budburst and maturity did not differ significantly in the case of Q. ilex. We suggest that the difference between δ13C of young leaves was linked to differential use of reserves of carbon compounds in the two species. 3.δ13C values of mature leaves were negatively correlated with minimum seasonal values of predawn water potential, suggesting that a functional adjustment to water resources occurred. 4. There was a significant correlation between individual δ13C values for two successive years. This interannual dependence showed that δ13C rankings between trees were constant through time.
Keywords: Biochemical content; isotope composition; leaf development; Quercus; water constraint

Adaptation and local validation in a Mediterranean environment of a process-level ecosystem model driven by remotely sensed inputs - Lacaze, B; Tabarant, F; Rambal, S (REMOTE SENSING `96: INTEGRATED APPLICATIONS FOR RISK ASSESSMENT AND DISASTER PREVENTION FOR THE MEDITERRANEAN, 1997)
A process-level ecosystem model (FOREST-BGC) has been used to simulate the short-term variability of functional processes and the slower responding allocation of photosynthesis products to plant components maintenance or growth, and to decomposition. The model emphasises Leaf Area Index (LAI) as a key structural attribute with substantial control over ecosystem process rates. Model simulations (soil water balance, photosynthesis, net primary production,...) have been obtained for a 10 years period (1984-1993) and partially validated with ground measurements from an experimental test site located in Southern France (dominant species: holm oak). Further work include scaling up from local to regional level, using remote sensing inputs and ancillary data.
Keywords: funtional processes; Holm oak; leaf area index; model simutalins; photosynthesis alocation; structural attribute

Between-tree variations in leaf Î´ 13 C of Quercus pubescens and Quercus ilex among Mediterranean habitats with different water availability - Damesin, C; Rambal, S; Joffre, R (Oecologia, 1997)
In this study, sun leaf carbon isotope compo- sition (d 13 C) of two co-occurring woody Mediterranean species (Quercus pubescens Willd., a deciduous oak, and Q. ilex L., an evergreen one) was investigated on four sites with dierent water availability. The total range of d 13 C values was 4.4 and 3.1& for Q. pubescens and Q. ilex respectively. The intra-site variability was about 3&. Total mean per species was equal. There were sig- ni®cant dierences among sites, but at each site means of d 13 C were not signi®cantly dierent between species. A simple physiological model predicts no dierence in in- trinsic water-use eciency (WUEi ) between evergreen and deciduous oaks. The relationship between site means of d 13 C and water parameters suggests that there is a leaf functional adjustment with respect to available water resource. No correlation was found between d 13 C and the contents of any mass-based biochemical cons- tituent. Nevertheless there was a signi®cant correlation between d 13 C and leaf mass per area of Q. ilex. For both species, there is also a positive correlation between leaf d 13 C and individual crown area, i.e. a structural char- acteristic at tree level. Causal relations between d 13 C and plant-environment interactions are discussed.
Keywords: carbon isotope composition; Foliar chemical constituents; mediterranean oaks; tree structure; Water availability

Modelling transpiration in holm-oak savannah: scaling up from the leaf to the tree scale - Infante, J M; Rambal, S; Joffre, R (Agricultural and Forest Meteorology, 1997)
The transpiration of oak-savannas in southern Spain was modelled by scaling-up from the leaf to the tree during a drought period. Two chlaracteristics of this ecosystem were found to facilitate the modelling procedure. The first was a near-zero decoupling coefficient between the surface and the surrounding bulk air, which simplifies the transpiration formulation. The second was that the surface conductance (g) is mainly related to the vapour pressure deficit of the air (0,). Based on both of these characteristics, the modelling procedure provides a general model of transpiration over the time scale appropriate for a drought period, from days to months. The response of g to 0, was found to follow a negative exponential function, such that beyo’nd a minimum value, g becomes independent of 0,. This implies a feedback control on g by 0,. The consequences of tbis control for transpiration were found at different levels of plant water status. This explains the plants’ adaptation to long dry periods, even though there is also continuous water loss during these periods. Such an adaptation was corroborated by a seasonal hysteresis found in the relationship between transpiration and D, as a function of the plants’ water status
Keywords: oak savannas; seasonal hysteresis; southern Spain; Transpiration; vapour pressure deficit

Drought and photosystem II activity in two Mediterranean oaks - Méthy, M; Damesin, C; Rambal, S (Ann. For. Sci., 1996)
The responses of photosystem II (PS II) to drought were analysed on two Mediterranean oak species, Quercus ilex and Q pubescens, using the chlorophyll fluorescence pulse-amplitude-modulation technique. The maximal PS II photochemical efficiency (Fv/Fm) of the evergreen Q ilex and the deciduous Q pubescens oaks was only affected when leaf predawn water potential was lower than -4 MPa. This value is rarely observed on mature trees growing in the field, but can be undergone by young seedlings during drought periods, hence confirming the stability of PS II. Whatever the irradiance, drought resulted, in both species, in lower values of PS II photochemical efficiency in a light-adapted state (ΔF/F m'), due to stomatal closure and/or a direct inhibition of the dark reactions of photosynthesis. Diurnal decreases of Fv/Fm of 30 min dark-adapted leaves were greater for lower predawn water potential; a recovery was observed in the late afternoon. The reversible decreases in the diurnal time-courses of maximal fluorescence led us to assume the onset of protective mechanisms from permanent photodamages in Q ilex and, to a lesser extent, in Q pubescens.
Keywords: fluorescence; photoinhibition; Photosystem II; Quercus; water stress

Effects of elevated carbon dioxide on leaf gas exchange and growth of cork-oak (Quercus suber L) seedlings - Damesin, C; Galera, C; Rambal, S; Joffre, R (Ann. For. Sci., 1996)
Leaf gas exchange and growth were determined on cork-oak (Quercus suber L) seedlings which were grown from acorns for periods of up to 4 months in greenhouses at ambient (350 μmol mol-1) and at elevated (700 μmol mor-1) concentrations of carbon dioxide. In well-watered conditions, daily maximum photosynthesis (15 μmol m-2 s -1) and stomatal conductance (440 mmol m-2 s-1) of plants grown and measured at 700 μmol mol-1 CO2 did not differ from those of plants grown and measured at 350 μmol mol-1. In conditions of moderate drought, net CO2 assimilation was at least twice as great in elevated CO2, but stomatal conductance was unchanged. Elevated CO2 affected total biomass production, the average increase being 76 and 97% at 3 and 4 months, respectively. Shoot biomass, root biomass, stem height and total leaf area were increased by elevated CO2. Root and stem ramification were also enhanced by elevated CO2, but no change in root/shoot ratio was observed.
Keywords: Carbon dioxide; Growth; photosynthesis; Quercus suber; Stomatal conductance

Local variations of ecosystem functions in Mediterranean evergreen oak woodland - Joffre, R; Rambal, S; Romane, F (Ann. For. Sci., 1996)
The spatial variation of ecosystem function was studied in a Quercus ilex coppice growing on hard limestone with low soil water availability. Spatial structures obtained from data on i) leaf area index, ii) leaf litterfall, and iii) leaf litter decay rate were compared. All these variables were sampled on 26 points located within a 30 x 30 m plot. Mean average leaf litterfall over 10 years (1984-1993) was 254 g.m-2. For each year, the semivariograms of leaf litterfall have been fitted using a spherical model. The values of the range parameter (indicating the limit of the spatial dependence) ranged from 6.4 to 10.3 m, very close to the value (9.2 m) of the range parameter obtained when fitting the semivariogram of mean leaf litterfall over 10 years. This result indicates the temporal persistence of the spatial pattern of leaf litterfall. The leaf area index (LAI) was estimated at the same points with a plant canopy analyzer. The mean value was 2.96 ± 0.30. The limit of spatial dependence for LAI was very close to that obtained for leaf litterfall (range = 8.5 m). The litter decomposition pattern was obtained through analysis of litter samples taken at the same points. The percentage of ash-free litter mass remaining (LMR) estimated using near-infrared reflectance spectroscopy indicates the stage of decomposition. It decreased strongly between the surface (mean value 85.6%) and the subsurface layers (mean value 63.4%). The two semivariograms can be described by spherical models, the sill being reached at a range of 21.4 and 18.7 m for the surface and subsurface layers, respectively. The two variables directly related to the structure of the canopy (LAI and leaf litterfall) exhibited close spatial dependence and differed from the soil process-related variables (stage of decomposition) whose ranges were approximately double. These geostatistical analyses show promise for use in developing hypotheses concerning the spatial scale of process-pattern interactions.
Keywords: decomposition; geostatistics; leaf area index; litterfall; local variation; Quercus ilex

Optimization of carbon gain in canopies of Mediterranean evergreen oaks - Rambal, S; Damesin, C; Joffre, R; Méthy, M; Lo Seen, D (Ann. For. Sci., 1996)
The main goal of this study was to analyze the depth-distribution of leaf mass per area (LMA) measured in ten canopies of Mediterranean evergreen oaks, five canopies of Quercus coccifera and five canopies of Q ilex, across soil water availability gradients in southern France, Spain and Portugal. There was a significant site effect on LMA with values being lower in mesic sites compared to those on xeric sites. In all canopies, LMA decreased by up to 50% from the top to the bottom. The relationships between cumulative leaf area index and LMA could be represented by an exponential function. For two canopies of Q ilex growing in contrasting environments, we analyzed the interrelationships among LMA, mass-based nitrogen, mass-based metabolic versus structural (total fiber) content, photosynthetic electron transport and carbon isotope composition. There was no difference in mass-based nitrogen or fiber content among upper and lower canopy positions in both locations. The maximum quantum yield of linear electron flow can be considered to be constant within the canopy. The area-based maximal electron transport rate and the carbon isotope composition were significantly linearly related to the LMA. Finally, we tested whether the observed depth-distribution follows the pattern suggested by some optimization theories.
Keywords: Leaf mass per area; Mediterranean evergreen canopy; photosynthesis-related leaf property; Quercus coccifera; Quercus ilex

HOW TREE COVER INFLUENCES THE WATER-BALANCE OF MEDITERRANEAN RANGELANDS - Joffre, R; Rambal, S (ECOLOGY, 1993)
Dehesa ecosystems of the southwestern Iberian Peninsula are characterized as a savanna-like rangeland dominated by scattered mediterranean evergreen oak trees. We investigated whether isolated trees modify the water balance of this ecosystem and if so, what implications this finding might have on models that assume homogeneity of soil water resources. The water balance of the two ecological components of the dehesas-(1) the tree-grass component, and (2) the open areas between the tree canopies with unshaded grass vegetation-was studied for three consecutive years in three locations in the Sierra Norte de Sevilla region of Andalusia in southern Spain. In this region, annual rainfall was generally between 600 and 800 mm, and the summer drought lasted almost-equal-to 130 d. Soil water storage was measured with a neutron moisture gauge outside and under the tree canopy. Deep drainage between two consecutive census dates was calculated using field-measured drainage characteristics. Evapotranspiration (Ea) and surface runoff were computed from the water balance equation assuming that Ea is limited by Penman potential evapotranspiration. Monthly Ea by annual species in open areas was poorly correlated with rainfall levels in the autumn and was limited during the spring by availability of water in the top 40 cm of soil. During summer, monthly Ea by trees ranged from 30 to 50 mm. Mean annual Ea was 400 mm outside and 590 mm under the tree cover. In open areas, water yield (WY), defined as the sum of deep drainage and surface runoff, ranged from 65 to 100% of total Ea, whereas under the tree canopy WY was only 20 to 40% of the Ea. Under the tree canopy, when annual precipitation was < 570 mm, WY was negligible and all precipitation was lost by evapotranspiration. Outside the tree canopy, WY occurred as soon as annual precipitation exceeded 250 mm. Models of competition between trees and grass generally assume a spatial homogeneity of soil hydrodynamic properties. Our results, however, show that both soil water storage and evapotranspiration are greater for the tree-grass component. Consequently, these models must account for this spatial variability in water resources according to species.
Keywords: DEEP DRAINAGE; Dehesa; Evapotranspiration; Grasses; hydrological equilibrium; MEDITERRANEAN OAK WOODLANDS; Quercus ilex; Quercus-suber; surface runoff; Trees; water balance

Évolution du potentiel hydrique foliaire et de la conductance stomatique de quatre chênes méditerranéens lors d'une période de dessèchement - Acherar, M; Rambal, S; Lepart, J (Ann. For. Sci., 1991)
Influence of soil drying on leaf water potential and stomatal conductance in four Mediterranean oak species. The water relations and the responses of 2 evergreen Quercus species (Quercus ilex L and Q suber L) and 2 deciduous species (Q afares Pomel and Q faginea Willd) were studied under experimental conditions. Two-yr old seedlings grown in 30-1 pots were subjected to a drying period where stomatal conductance, pre-dawn leaf water potential and minimum leaf water potential were measured. The results show that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al (1978, 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance (gsr max) as described by the reciprocal function gsr max = (-0.47 + 2.61 ψb)-1 for the evergreen oaks and gsr max = (-1.94 + 7.39 ψb)-1 for the deciduous ones. The differences between the 2 groups may partially explain their geographic distributions, and also lead to general questions concerning the mechanisms of water use in the Mediterranean oak species.
Keywords: deciduous; evergreen; mediterranean species; Quercus; Stomatal conductance; water potential; water stress